ANALISIS RELEVANSI HIPOTESIS KUZNET TERHADAP KETIMPANGAN PENDAPATAN DI INDONESIA PERIODE 2004-2023 - Aqil Usman Hermawan; Arivina Ratih Yulihar Taher (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
This study examines factors influencing income inequality in Indonesia and tests the Kuznets Hypothesis from 2004 to 2023 using panel data from 33 provinces. The analysis applies the Fixed Effect Model (FEM), chosen through Chow and Hausman tests, while checking for classical assumptions like normality, multicollinearity, and heteroscedasticity. Key variables include Gross Regional Domestic Product (GRDP), its square to test the Kuznets Hypothesis, Human Development Index (HDI), Gross Fixed Capital Formation (GFCF), Open Unemployment Rate (OUR), and Poverty Rate (PR). Results show that GRDP positively affects inequality, while its square negatively impacts it, supporting the inverted U-curve theory. HDI reduces inequality, whereas GFCF increases it, suggesting investment concentration widens the gap. OUR and PR both decrease inequality, indicating more equal income distribution in areas with lower welfare. The study highlights the need for inclusive growth, equitable human development, and fair investment distribution to reduce inequality.